Arabic Language and Islamic Values: Bridging Ethnic Diversity for National Development in Nigeria - Taofeek Olalekan Yusuf; Rahman Adewale Abdul Azeez; Isiaka Adewale Lawal; Mikail Adebisi Folorunsho (ALSINATUNA, 2025)
The need for national development and peaceful coexistence amongst the citizenry dominated current discussion in Nigeria. The article examined the impacts of Arabic language and Islamic values in the actualization of national development in Nigeria via the bridging of ethnic diversity. The paper critically examined factors that constitute obstacles to unity amongst Nigerians, with a view to finding panaceas to Nigeria’s imminent disintegration. This study, using a qualitative approach employed both historical and contextual methods to investigate the causes of disunity where ethnic diversity exists. It examined the predisposing factors as well steps that could be taken to ensure peaceful co-existence and national development. Data were collected from a range of reliable published sources in Arabic language authored by eminent Nigerian Arabic scholars intermarried with case studies of the current situation. The study revealed that doctrinal differences, leadership tussle, tribal affiliations, and matters relating to political leadership are some of the major contentious issues. The results indicated that literacy in Arabic language and deeper understanding of Islamic values have the potentialities of  serving as the vehicles in facilitating harmonious relationship and national development. The knowledge of Arabic stimulates interaction at the linguistic level both in local and international contexts and promotes unity amongst the citizenry, together with Islamic values. They jointly play an important role in peacemaking and national development. Subsequent studies must explore further,  the impact of Arabic education in peacemaking amongst the citizens of diverse backgrounds and advise the educators on the need for  curriculum development to improve the level of harmonious relationship amongst Nigerians. Considering the fact that the corporate existence of Nigeria is preferable to its disintegration, the study provided a list of recommendations the actualization of which could enhance the much-desired national development.